2018
DOI: 10.1002/jctb.5510
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical recovery of copper complexed by DTPA and C12‐DTPA from aqueous solution using a membrane cell

Abstract: BACKGROUND The electrochemical recovery of copper from diethylenetriaminepentaacetic acid (DTPA) and C12–DTPA (a surface‐active derivative of DTPA) complex solutions was investigated in a membrane flow cell. Electrolysis time, solution flow rate, applied current density, and solution pH were evaluated. RESULTS The chelating surfactant C12‐DTPA can promote the kinetics of copper electrodeposition more than DTPA depending on the experimental conditions. At a current density of 30 A m–2, a solution flow rate of 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…However, the technique is not efficient for treating concentrated solutions and some of the collectors might not be suitable to use from an economic and/or environmental point of view [28]. Recent studies although, showed that the stripping of the collected metals and the re-use of the collector is possible [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…However, the technique is not efficient for treating concentrated solutions and some of the collectors might not be suitable to use from an economic and/or environmental point of view [28]. Recent studies although, showed that the stripping of the collected metals and the re-use of the collector is possible [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…Although the ion otation of zinc and lead has already been investigated, it has barely been tested under realistic conditions. 32,36,[45][46][47][48] The interpretation of experimental data from synthetic solutions to real ones might prove problematic, due to the complexity of the chemical matrix of hydrometallurgical leachates.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some of the commercial available surfactants and the chemicals used might be expensive and/ or toxic [19,20]. Nevertheless, laboratory studies showed that the regeneration of the chemicals used in foam separation techniques is possible, which can make them more attractive from an economical and environmental point of view [19,[21][22]. To the best of our knowledge only ion flotation has been employed so far on industrial scale for the purification of wastewater from textiles and for the recovery of tungsten and molybdenum from smelter wastewater [20].…”
Section: Introductionmentioning
confidence: 99%